ANALISIS ANTARMUKA SISTEM INFORMASI AKADEMIK (SIAKAD) UNIVERSITAS MAJALENGKA MENGGUNAKAN METODE EVALUASI HEURISTIK - Nida, Milhatun; Wahid, Abrar; Aros , Desfi Silvia; Winata , Satria (Universitas Majalengka, 2025)
This study evaluates the Academic Information System (SIAKAD) interface at Universitas Majalengka using the Heuristic Evaluation method to identify usability issues. The evaluation focuses on two main scenarios, namely the login process and access to the Study Result Card (KHS). The evaluation was conducted by three independent evaluators based on Jakob Nielsen's ten heuristic principles Nielsen. The findings show that there are four usability issues, with three issues categorized as high priority (major) and one issue as low priority (minor). The main issues were found on the login page in the form of uninformative error messages and password text that was not visible to users. Additionally, inconsistencies were found in the navigation access to KHS, which is still integrated with the Course Registration History page. These findings indicate the need for clear error messages, a redesign of the information architecture, and the addition of modern support features to enhance the user experience. This research opens up opportunities for further testing using methods that involve direct users to comprehensively validate the findings. The recommended improvements are expected to increase the effectiveness, efficiency, and user satisfaction in the overall use of the SIAKAD at the University of Majalengka.